Penerapan Metode Demonstrasi Dan Diskusi Untuk Meningkatkan Pemahaman Konsep Mahasiswa Pada Materi Tumbukan - Dwi Aprillia Setia Asih; Indica Yona Okyranida; Erni Mariana (Navigation Physics : Journal of Physics Education, 2022)
Demonstration and discussion methods can stimulate students to be more active in the learning process. The application of demonstration and discussion methods is expected to increase student interest and activity in learning whose purpose is to increase students' understanding of concepts. This research was conducted in the odd semester of 2021/2022.  The research method used is quasi-experimental. Based on the analysis and discussion that has been carried out, it can be concluded that there is a significant difference in understanding of concepts between the experimental class and the control class. This is strengthened by the results of the independent sample t-test analysis, namely between the experimental class and the control class obtaining a significance of 0.001 below 0.005, in other words, learning using demonstration and discussion methods affects the understanding of student concepts. Thus, it can also be concluded that the understanding of student concepts can be improved by the application of demonstration and discussion methods.